Factors and future scenarios for green transition in circular waste management business model development - Noorhan Firdaus Pambudi; Togar Mangihut Simatupang; S.M. Samindi M.K. Samarakoon; Nur Budi Mulyono; R.M. Chandima Ratnayake; Liane Okdinawati (Journal of Open Innovation: Technology, Market and Complexity)
The research focuses on the challenges and factors influencing the development of circular waste management business models (CWMBM) in Indonesia, highlighting the reliance on landfills and the need for a transition towards more sustainable practices. Previous studies showing the relationship between factors for the implementation of a circular economy have been widely conducted but have neglected the discussion of factor priorities based on the influence of these factors on other factors, especially for the green transition towards a circular economy in waste management. This study aims to delineate the prioritisation of factors influencing the circular waste management business model, based on their impact on other factors. This study employed multiple case studies, causal loop diagrams (CLD), and the DEMATEL method to prioritize factors influencing the transition to a circular business model in green waste management, ultimately identifying sustainable risks and achievable Sustainable Development Goals (SDGs). Key findings revealed that community willingness to segregate waste significantly impacts separable waste collection service demand, costs, and waste workers health risks, while the analysis highlights the importance of integrating economic factors like profit into waste management business models to facilitate a green transition. The development of circular waste management businesses prioritizes factors such as waste segregation and service costs in the collection phase. In the prevention and waste reduction phase, the willingness to reduce waste and use plastic packaging is prioritized. Composting food waste is the primary factor in waste disposal and reprocessing phase. Profit is always the primary focus in all phases.